2013
DOI: 10.1007/s13594-013-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digestive enzymes on antimicrobial, radical scavenging and angiotensin I-converting enzyme inhibitory activities of camel colostrum and milk proteins

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 44 publications
6
55
0
Order By: Relevance
“…Salami et al (2008) reported higher extent of hydrolysis of camel caseins than that of bovine caseins upon treatment with pancreatic enzymes. Antimicrobial, radical-scavenging and angiotensin lconverting enzyme inhibitory activities of camel milk have also been studied by Jrad et al (2014), after hydrolysis by pepsin and pancreatin. Despite that, recent studies suggested that camel milk could have significant therapeutic attributes such as anti-cancer and anti-diabetic properties (Agrawal et al 2003;Magjeed 2005), search for milk-based bioactive peptides has been focused until now mainly on bovine and to smaller extent on ovine and caprine milk proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Salami et al (2008) reported higher extent of hydrolysis of camel caseins than that of bovine caseins upon treatment with pancreatic enzymes. Antimicrobial, radical-scavenging and angiotensin lconverting enzyme inhibitory activities of camel milk have also been studied by Jrad et al (2014), after hydrolysis by pepsin and pancreatin. Despite that, recent studies suggested that camel milk could have significant therapeutic attributes such as anti-cancer and anti-diabetic properties (Agrawal et al 2003;Magjeed 2005), search for milk-based bioactive peptides has been focused until now mainly on bovine and to smaller extent on ovine and caprine milk proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have been reported that camel colostrum is rich in bioactives molecules such as antioxydant and antihypertensif peptides released after enzymatic hydrolysis or fermentation of milk (Jrad et al, 2014). Among the bioactive fragments, antimicrobial peptides (AMP) attract the attention of many researchers because the resistance of many pathogenic bacteria to conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been elucidated that many peptide sequences in milk proteins have angiotensin-converting enzyme (ACE)-inhibitory activity (Jrad et al 2014;Otte et al 2007). The angiotensin I-converting enzyme (ACE, EC 3.4.15.1) is a dipeptidyl carboxypeptidase which regulates the blood pressure (Hooper 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although the bioactivity of the milk-derived peptides from different sources has been extensively studied, only few attempts have been made to investigate the peptides from camel milk proteins (Jrad et al 2014;Moslehishad et al 2013;Salami et al 2011). Jrad et al (2014) hydrolyzed the camel milk protein by pepsin and pancreatin and evaluated the antioxidant and ACE-inhibitory activities of resulting peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation